A history of tourism, leisure and adventure in the Antarctic and Sub-Antarctic, c.1895 to present - Hanekom, Wouter Pierre (Stellenbosch : Stellenbosch University, 2014)
Thesis (MA)--Stellenbosch University, 2014.